Does Economic Development Affect Public Debt Accumulation ? Empirical Evidence from India - Saini, Pratibha; Muniyoor, Krishna (Indian Journal of Finance, 2022)
The main aim of this paper was to explore various public debt determinants in India using structural equation modeling (SEM). This study is based on secondary data, starting from 1985 – 2018. The study was partially confirmatory and partially exploratory as it also inspected the interaction between economic development and public debt. The findings suggested that, among various macroeconomic variables, debt servicing, inflation, and military expenditure are the key determinants of debt in India. Moreover, as expected, economic development has a negative relation with public debt, suggesting that public debt accumulation tends to decrease with the progress in economic development. It is acknowledged that the improvement in socioeconomic conditions is likely to enhance the overall welfare of the people and thereby create more productive resources in the economy. Therefore, from a policy perspective, we should zero in on internal and debt-related factors.